Synchronizing estrus in beef heifers with prostaglandin and syncromate B - DeBenedetti, R.C.; Kiracofe, G.H.; Hultine, V.; McKee, R.M.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Forty-five of 50 heifers were in estrus 1 to 5 days after 7-day synchronization implants were removed. Prostaglandin was injected one day before implants were removed. Thirty-one of the 45 (68.9%) heifers conceived to first artificial insemination service.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Synchronize; Prostaglandin; Syncromate B